2012
DOI: 10.1111/jai.12015
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships of freshwater fishes from the western part of Anatolia, Turkey

Abstract: Summary Length–weight relationships were calculated for nine freshwater fish species belonging to two families using 1020 specimens from 15 water sources in the western part of Anatolia, Turkey. This study is the first reference on length–parameters for these species, eight of which are endemic, and with new maximum length records for three of the species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 8 publications
4
15
1
Order By: Relevance
“…In this study, L. kotellati showed isometric growth (n = 11, b = 2.8825) which was consisted with previous studies (Gaygusuz et al, 2013). Only one study reported allometric growth (b = 3.138) for this species in Turkish inland waters (Başıaçık et al, 2012) (Table 3).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, L. kotellati showed isometric growth (n = 11, b = 2.8825) which was consisted with previous studies (Gaygusuz et al, 2013). Only one study reported allometric growth (b = 3.138) for this species in Turkish inland waters (Başıaçık et al, 2012) (Table 3).…”
Section: Discussionsupporting
confidence: 85%
“…A recent study, allometric growth (b = 3.017) was reported for C. baliki from Sakarya River (Gaygusuz et al, 2013). Ayyildiz et al (2014), studied age and growth of C. erhani in Menzelet Reservoir, Ceyhan River drainage and it was reported that growth of C. erhani is positive allometric for males (b = 3.2011), isometric for females (b = 3.0015) and allometric (b = 3.0892) for combined sex (Table 3).…”
Section: Discussionmentioning
confidence: 95%
“…For B. pergamonensis, Gaygusuz et al (2013) previously reported a maximum TL of 20.9 cm; the specimens of 22.9 cm caught from the Tersakan River in the present study represent the new maximum reported TL for the species. For C. bergamae, an earlier maximum TL of 28.8 cm was stated (Gaygusuz et al, 2013), but in the samples analyzed during the present research, a new maximum TL of 34.8 cm was recognized from the Tersakan River. Although these large specimens could be unusual, these results have underlined the current lack of data on these species.…”
Section: Discussionsupporting
confidence: 62%
“…Because of the lack of information, B. pergamonensis has been assessed as "data deficient" in the Red List of threatened and declining species of Turkey (Fricke et al, 2007). The only information on B. pergamonensis reported in the literature indeed refers to its distribution area (Stoumboudi et al, 2006;Kottelat and Freyhof, 2007) and a length-weight equation of the species (Gaygusuz et al, 2013;Erk'akan et al, 2014). Although currently no other data on the biology of this species are available, the species is assessed as being of "least concern" according to the IUCN Red List of Threatened Species (Freyhof and Kottelat, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation